2018
DOI: 10.1111/jocn.14586
|View full text |Cite
|
Sign up to set email alerts
|

Preconception care for infertile couples: Nurses’ and midwives’ roles in promoting better maternal and birth outcomes

Abstract: We argue that, by providing preconception care, nurses and midwives have an opportunity to deliver important advice to infertile couples in both primary care and specialist infertility services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…midwives and maternal and child health nurses) could play a role in the continuum of preconception care, particularly between pregnancies. [32][33][34][35] Consideration of promising innovative digital solutions such as interactive conversational agents as an adjunct to face-to-face care could also be trialled to overcome some of the noted barriers in the delivery of preconception care. 36 Given our findings, further exploration of these models of care and extending the scope of practice for these professionals is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…midwives and maternal and child health nurses) could play a role in the continuum of preconception care, particularly between pregnancies. [32][33][34][35] Consideration of promising innovative digital solutions such as interactive conversational agents as an adjunct to face-to-face care could also be trialled to overcome some of the noted barriers in the delivery of preconception care. 36 Given our findings, further exploration of these models of care and extending the scope of practice for these professionals is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 It is important that evaluation of the feasibility and effectiveness of such approaches take into account models of care addressing the constraints identified by primary care providers. 8,9,[32][33][34][35]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, nurses` familiarity regarding BFRs can play an important role in reducing exposures of vulnerable groups. Providing preconception care, including information on environmental health by nurses and midwives has been recommended as a measure to improve the chances of conception and to optimize pregnancy outcomes [26]. Because BFRs have been associated with an increased risk of infertility [27] and spontaneous abortion [28], nurses can advise future parents about sources of emission and ways to reduce exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The Implication to Nursing Practice Allan et al (2018) found that the needs of infertile couples for preconception care are often overlooked. Nurses have the opportunity to identify and address these needs during infertility investigations and assisted conception planning.…”
Section: Educational Interventionmentioning
confidence: 99%